Molecular characterization of adenosine monophosphate deaminase 1 and its regulatory mechanism for inosine monophosphate formation in triploid crucian carp - Zhou, Yonghua; Zuo, Anli; Li, Yingjie; Zhang, Yu; Yi, Zilin; Zhao, Dafang; Tang, Jianzhou; Qu, Fufa; Cao, Shenping; Mao, Zhuangwen; Jin, Junyan; Liu, Zhen (Frontiers in Physiology, 2022)
Inosine monophosphate (IMP) is the main flavoring substance in aquatic animal, and adenosine monophosphate deaminase1 (AMPD1) gene is a key gene in IMP formation. At present, the research on the mechanism of AMPD1 regulating IMP formation in aquatic animal is still blank. In this study, in order to study the mechanism of AMPD1 regulating IMP formation in fish, the full open reading frame (ORF) of AMPD1 which was 2160bp was obtained for the first time in triploid crucian carp (Carassius auratus). It encoded 719 amino acids with a molecular mass of 82.97kDa, and the theoretical isoelectric point value was 6.31. The homology analysis showed that the homology of triploid crucian carp and diploid Carassius auratus was the highest, up to 99%. And the phylogenetic tree showed that triploid crucian carp was grouped with diploid Carassius auratus, Culter alburnus and Danio rerio. And real-time fluorescence quantitative results showed that AMPD1 was expressed specifically in muscle of triploid crucian carp(P<0.05). The results of detection the localization of AMPD1 in cells indicated that the AMPD1 was mainly localized in cytoplasm and cell membrane. Further, we examined the effects of glutamate which was the promotor of IMP formation on the expression of AMPD1 and the formation of IMP in vivo and in vitro experiments, the results showed that 3% glutamate and 2mg/mL glutamate could significantly promote AMPD1 expression and IMP formation in triploid crucian carp muscle tissue and muscle cells(P<0.05). Then we inhibited the expression of AMPD1 in vivo and in vitro experiments, we found the formation of IMP in muscle tissue and muscle cells of triploid crucian carp all were inhibited and they affected the gene expression of AMPK-mTOR signaling pathway. The all results showed that AMPD1 mediated glutamate through AMPK-mTOR signaling pathway to regulate the formation of fish IMP.